Espacialização e dinâmicas contemporâneas da agropecuária paranaense - Cecília Hauresko; Hervé Théry (Confins)
Technological revolution is providing the intensification of the capitalist way in producing in agriculture, promoting real restructuring in the sector. From this, new agricultural spaces can be incorporated into the globalized production and consumption, while others keep with the traditional system. In this connection, the work tries to understand the characteristics of the familiar and employer agriculture, highlighting these different patterns at agriculture and cattle-raising in the distinct regions of the state of Paraná. For this, with the Brazilian Institute of Geography and Statistics (IBGE) data basis systematization – Agriculture and Cattle raising municipal production in 2014/2015, and generation of maps on this, identify the agriculture territory organization in Paraná. The results show, undoubtedly, the territory is divided into regions and areas where they look for expertise, supported by the science, techniques, and information (commodities). Otherwise, in others, they resist with traditional techniques in food production. This inequality creates a conflicting agricultural scenario in relation to the use and ownership of the land.